International consensus on the assessment of bruxism: Report of a work in progress. (21st June 2018) - Lobbezoo, F.; Ahlberg, J.; Raphael, K. G.; Wetselaar, P.; Glaros, A. G.; Kato, T.; Santiago, V.; Winocur, E.; De Laat, A.; De Leeuw, R.; Koyano, K.; Lavigne, G. J.; et al.
Summary: In 2013, consensus was obtained on a definition of bruxism as repetitive masticatory muscle activity characterised by clenching or grinding of the teeth and/or by bracing or thrusting of the mandible and specified as either sleep bruxism or awake bruxism. In addition, a grading system was proposed to determine the likelihood that a certain assessment of bruxism actually yields a valid outcome. This study discusses the need for an updated consensus and has the following aims: (i) to further clarify the 2013 definition and to develop separate definitions for sleep and awake bruxism; (ii) to determine whether bruxism is a disorder rather than a behaviour that can be a risk factor for certain clinical conditions; (iii) to re‐examine the 2013 grading system; and (iv) to develop a research agenda. It was concluded that: (i) sleep and awake bruxism are masticatory muscle activities that occur during sleep (characterised as rhythmic or non‐rhythmic) and wakefulness (characterised by repetitive or sustained tooth contact and/or by bracing or thrusting of the mandible), respectively; (ii) in otherwise healthy individuals, bruxism should not be considered as a disorder, but rather as a behaviour that can be a risk (and/or protective) factor for certain clinical consequences; (iii) both non‐instrumental approaches (notably self‐report) and instrumental approaches (notably electromyography) can be employed to assess bruxism; and (iv) standard cut‐off points for establishing the presence or absence of bruxism should not be used in otherwise healthy individuals; rather, bruxism‐related masticatory muscle activities should be assessed in the behaviour's continuum.